2023
DOI: 10.3389/fsurg.2022.1049534
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of different surgical approaches to hemiarthroplasty for the femoral neck fractures: A meta-analysis

Abstract: There are three traditional surgical approaches to hemiarthroplasty (HA) for femoral neck fractures, respectively, the anterior approach (AA), the lateral approach (LA) and the posterior approach (PA). However, the optimum approach is still controversial, the purpose of this meta-analysis is to identify the merits and demerits of all three approaches. All clinical published studies in PubMed, Web of Science, Embase, and the Cochrane Library from January 2000 to April 2022 were searched which compared different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Prosthetic hip dislocation is a documented complication of all HA surgical approaches, with some data suggesting dislocation may be more commonly associated with a PA. Kunkel et al noted a significantly lower dislocation rate after a DAA HA for FNF than a PA among 9 pooled studies with 330 DAA and 108 PA 16 . Similar findings have been reported throughout retrospective and registry data, including among total hip arthroplasty (THA) literature 1,3,34,35 . However, the only network meta-analysis of RCTs comparing primary THA approaches found no difference in dislocation by final follow-up 36 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Prosthetic hip dislocation is a documented complication of all HA surgical approaches, with some data suggesting dislocation may be more commonly associated with a PA. Kunkel et al noted a significantly lower dislocation rate after a DAA HA for FNF than a PA among 9 pooled studies with 330 DAA and 108 PA 16 . Similar findings have been reported throughout retrospective and registry data, including among total hip arthroplasty (THA) literature 1,3,34,35 . However, the only network meta-analysis of RCTs comparing primary THA approaches found no difference in dislocation by final follow-up 36 .…”
Section: Discussionsupporting
confidence: 84%
“…24.00067 HA include the posterior approach (PA), anterolateral approach (ALA), direct lateral approach (DLA), and direct anterior approach (DAA). Each approach has its own complication profile and may influence pain or functional recovery differently [3][4][5][6] . Furthermore, the DAA has recently become popularized among HA surgical approaches.…”
mentioning
confidence: 99%
“…The surgical technique discussed in this paper utilises the direct lateral approach. Shuai at al., found that the posterior approach had a higher risk of dislocation and need for reoperation that the anterior and lateral approaches while the anterior approach had shorter lengths of hospitalisation and less postoperative pain [14]. Furthermore, Parker et al, concluded that rates of medical complications such as pneumonia, congestive cardiac failure and urinary tract infection, and mortality rates at six months, one year and two years, were higher in the posterior approach than the anterior approach while the anterior approach appeared to have a higher rate of pain at one month after surgery and impaired mobility [15].…”
Section: Hip Reduction and Completion Of Hemiarthroplastymentioning
confidence: 94%
“…There were no significant differences in infection, pulmonary embolism, myocardial infection, mortality rates, or need for a reoperation between hemiarthroplasties and total hip arthroplasties [13]. Furthermore, hip hemiarthroplasties can be conducted from an anterior approach, a direct lateral approach or a posterior approach [14]. The surgical technique discussed in this paper utilises the direct lateral approach.…”
Section: Hip Reduction and Completion Of Hemiarthroplastymentioning
confidence: 98%